TLR2 promotes human intrahepatic cholangiocarcinoma cell migration and invasion by modulating NF‐κB pathway‐mediated inflammatory responses. (30th September 2016) - Liu, Bingyan; Yan, Shuo; Jia, Yiping; Ma, Jun; Wu, Shaoqiu; Xu, Yuyao; Shang, Mingyi; Mao, Aiwu
Abstract : Intrahepatic cholangiocarcinoma (ICC) is a rare and aggressive malignancy that is often diagnosed at advanced stages, which limits treatment options. Despite its increasing incidence and mortality worldwide, the pathogenesis of ICC is not well understood. Here, we examined the effect of the dysregulation of innate immune responses on carcinogenesis by investigating the role of toll‐like receptor (TLR)2 in the pathogenesis and invasiveness of ICC and explored the underlying mechanisms. Immunohistochemical analysis, real‐time PCR, and western blotting showed higher TLR2 levels in ICC tissues and cell lines. Silencing and overexpression experiments indicated that TLR2 promotes ICC migration and invasion, induces the expression of epithelial‐to‐mesenchymal transition (EMT) markers, and upregulates the proinflammatory cytokines tumor necrosis factor (TNF)‐α, interleukin (IL)‐6, and IL‐1β concomitant with the activation of NF‐κB signaling. Inhibition of NF‐κB activity abolished the effect of TLR2 on EMT, invasion and migration, and the TLR2‐induced upregulation of proinflammatory cytokines, and suppressed the effect of exogenous TNF‐α and IL‐6 on restoring EMT, migration and invasion in the presence of TLR2. Taken together, our results indicate that TLR2 has protumorigenic and prometastatic effects in ICC through the upregulation of inflammatory cytokines induced by the activation of NF‐κB signaling, suggesting potential novel therapeutic targets for the treatment of ICC. Abstract : The significantly higher levels of TLR2 in tumor tissues and intrahepatic cholangiocarcinoma (ICC) cell lines led us to investigate the role of TLR2 in ICC. We found that TLR2 promotes ICC migration and invasion, and induces the expression of epithelial‐to‐mesenchymal transition (EMT) markersthrough the upregulation of inflammatory cytokines induced by the activation of NF‐κB signaling.